Interpretation of pediatric lung function: Impact of ethnicity12. Issue 1 (19th March 2012) - Kirkby, J.; Bonner, R.; Lum, S.; Bates, P.; Morgan, V.; Strunk, R.C.; Kirkham, F.; Sonnappa, S.; Stocks, J.
Abstract Rationale To evaluate the appropriateness of spirometric and plethysmographic reference equations in healthy young children according to ethnic origin. Methods Spirometry data were collated in 400 healthy children (214 Black and 186 White) aged 6–12 years. Of these children, 68 Black and 115 White children also undertook plethysmography. Results were expressed as percent predicted according to commonly used equations for spirometry and plethysmography. Results Black children had lower lung function for a given height compared to White children. The magnitude and direction of these differences varied according to specific outcome. In the studied age range (6–12 years) the ethnic‐specific Wang equations were adequate for spirometry (mean results approximating 100% predicted in both ethnic groups). By contrast, significant differences were found between observed and % predicted plethysmographic lung volumes according to published equations derived from White children: Among the Black children, function residual capacity (FRC) and total lung capacity (TLC) were on average, 14 and 6% lower than predicted, whereas mean residual volume (RV) and RV/TLC were 4 and 10% higher. Among White children, the Rosenthal equations gave the best fit, with the exception of FRC which was, on average, 9% lower than predicted. Conclusion Spirometry equations may suffice in Black children; however, interpretation of static lung volumes in Black children is limited due to inappropriate reference equations. More appropriate plethysmographic reference equations that are applicable to all ethnic groups across the entire age range are urgently needed. Pediatr Pulmonol. 2013; 48:20–26. © 2012 Wiley Periodicals, Inc.